2011
DOI: 10.1111/j.1755-3768.2011.2376.x
|View full text |Cite
|
Sign up to set email alerts
|

A biocornea of fish scales – First results of a research model

Abstract: Purpose To develop an animal model suitable to evaluate the biocompatibility of a fish‐scale derived biocornea. This biocornea has been developed as an alternative for the use of human tissue to replace damaged corneas. Prior to its use in humans, it is essential to determine the behavior and biocompatibility of the biocornea with the natural cornea. Methods A ±250 µm thick, decellularized and decalcified fish scale‐derived collagen matrix was implanted into the corneas of three groups of Fischer 344 male albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The FSS is primarily built of collagen type I, similar to the corneal stroma, so the attachment of the scaffold is expected to happen similarly. Also, transparency of FSS was acceptable and it did not degrade in vivo in any of the previously published studies [ 8 10 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The FSS is primarily built of collagen type I, similar to the corneal stroma, so the attachment of the scaffold is expected to happen similarly. Also, transparency of FSS was acceptable and it did not degrade in vivo in any of the previously published studies [ 8 10 ].…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, its transparency and availability, that is, roughly 200 scales from one fish, make it an attractive biocompatible material for the generation of corneal epithelial cell grafts. Additional in vivo studies performed on rats and rabbits have demonstrated its potential as a deep anterior lamellar keratoplasty (DALK) alternative or to seal perforated corneas, respectively [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional in vivo studies performed on rats and rabbits have demonstrated its potential as a deep anterior lamellar keratoplasty (DALK) alternative or to seal perforated corneas, respectively. 61 However, a recent report suggested that the fish scale derived scaffold in its current form may not be ideal for the development of tissue engineered corneal endothelial constructs. 62 Although hCECs adhered to the surface of the scales, regional differences in cellular proliferation were observed.…”
Section: Biologically Derived Materialsmentioning
confidence: 99%
“…The substitute is cell-free and of high biocompatibility with host tissue to restore corneal function, thereby avoiding the rejection reaction and the need for long-term steroid use. van Essen et al [ 23 ] demonstrated safety, biocompatibility, and regenerative potential of pocket implantation of a fish scale in rat model. We report here the safety, detailed morphologic, and physiologic results from the 6-month followup of rabbit model.…”
Section: Introductionmentioning
confidence: 99%